The Anti-War Movement through Romanticism of the Hippies Culture on Vietnam War 65-73 - Dwi Mifta Nugroho; Muhammad J.B. Firdaus; Adam J. Wijaya (Jurnal Hubungan Internasional, 2020)
In this paper, the authors try to provide an overview of the new socialmovement variant, which is the anti-war movements initiated by hippies.The hippie culture developed rapidly in the 1960s in the United Statesand now has spread to the whole world through cultural globalization.Hippie Movement itself is a subculture movement that has a significantrole in forming a counter-culture in the United States. This movement’ssuccess cannot be separated from the support of the musicians ofthe world through popular culture that will be discussed in this paper throughcultural globalization.